Approaches to the school floor in the experience of Physical Education pibidians (Research, Society and Development, 2021)
The objective of this study was to investigate the representation of PIBID in the initial training of Physical Education teachers. Ten pibidians participated in the study, through the focus group. The interpretation of the information followed the guidelines of the content analysis. Five categories of analysis emerged from the results: 1) Admission to and permanence in the program, 2) Knowledge about the objectives of PIBID, 3) The university and daily school life, 4) The acquisition of teaching skills and competences and 5) The influence of PIBID on initial training. Based on the data presented, the importance of a theoretical-practical training is perceived, as well as the need for the insertion of the pibidians in daily school life, enabling experiences for the construction of competences for pedagogical practice and providing knowledge of the school reality. The results show that the PIBID represents an increase in the quality of initial training.